Extraction, Isolation and Nutritional Quality of Coffee Protein - Rewati Raman Bhattarai; Hayder Al-Ali; Stuart K. Johnson (Foods, 2022)
Coffee protein is reported to have high levels of branched-chain amino acids of value in sports nutrition and malnutrition recovery. However, data demonstrating this unusual amino acid composition are limited. We investigated the extraction and isolation of protein concentrates from coffee bean fractions, viz. green coffee, roasted coffee, spent coffee and silver skin, and determined their amino acid profile, caffeine content and protein nutritional quality, polyphenol content and antioxidant activity. Alkaline extraction/isoelectric precipitation gave lower concentrate yields and protein content than alkaline extraction/ultrafiltration. The protein concentrate from green coffee beans had a higher protein content than those from roasted coffee, spent coffee and silver skin, regardless of extraction method. The isoelectric precipitated green coffee protein concentrate had the highest in vitro protein digestibility and in vitro protein digestibility corrected amino acid score (PDCAAS). Silver skin protein concentrate had a very low digestibility and in vitro PDCAAS. In contrast to a previous finding, the amino acid levels in all coffee concentrates did not demonstrate high levels of branched-chain amino acids. All protein concentrates had very high levels of polyphenols and high antioxidant activity. The study suggested investigating coffee protein’s techno-functional and sensory attributes to demonstrate their potential applications in different food matrices.